2009
DOI: 10.1007/s00268-009-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Observational Tool for Assessing Surgical Flow Disruptions and Their Impact on Surgical Performance

Abstract: This research depicts the development and utility of a tool to analyze surgical flow disruptions in the cardiovascular operating room with satisfactory inter-rater reliability. This tool is an important first step in systematically categorizing and measuring surgical flow disruptions and their impact on patient safety in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 28 publications
3
69
1
Order By: Relevance
“…20,21 Although these studies have documented the frequency of different types of disruptions and their effects on the flow of surgical procedures, 21,22 our study is the first to link data on surgical disruptions to rates of adverse outcomes for surgical patients. We found that disruptions due to a lack of bariatric surgery familiarity and expertise among assistants and/or residents, as well as anesthesiologists and related clinical staff, were significantly associated with rates of serious complications.…”
Section: Discussionmentioning
confidence: 91%
“…20,21 Although these studies have documented the frequency of different types of disruptions and their effects on the flow of surgical procedures, 21,22 our study is the first to link data on surgical disruptions to rates of adverse outcomes for surgical patients. We found that disruptions due to a lack of bariatric surgery familiarity and expertise among assistants and/or residents, as well as anesthesiologists and related clinical staff, were significantly associated with rates of serious complications.…”
Section: Discussionmentioning
confidence: 91%
“…In general use for trauma patients were 4 bays in the ED, 2 CT imaging rooms, and 2 ORs, although others were available, and no record was taken of which were used. Events that disrupted the flow of the trauma care process were collected using a tablet personal computer data collection tool, 27 which provided the total number of FDs. Entry and exit times for the ED, CT imaging room, and OR were also recorded, which allowed treatment times and FD rates to be calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Thus allowing clinicians to view their video recorded practices may be of help in sustaining best performances. Additionally, video recording can allow analysis of relationships and interactions without being impacted by the memory of an individual 76 82 83…”
Section: Discussionmentioning
confidence: 99%